Pendampingan Pencatatan Laporan Keuangan Pesantren Untuk Meningkatkan Kualitas Laporan Keuangan Pesantren - Riyan Laili; Hasana Hasan; Halimatut Tamimah; Anisa Nur Lathifah; Sherly Mega Paranti; Fakhri Siddiqi (Journal of Innovative and Creativity, 2025)
The financial report recording assistance activity in Islamic boarding schools (pesantren) is one form of the implementation of the Field Work Practice (PKL) program, which aims to help pesantren institutions in preparing accurate, transparent, and accountable financial reports. This activity was carried out at BUMPES Nurul Jadid, a pesantren business unit engaged in the economic empowerment of the santri community. In this program, students played an active role by providing technical guidance on daily transaction recording, cash report preparation, and assisting in the development of simple financial reports based on basic accounting principles. The implementation methods included observation, interviews, training, and direct mentoring of the pesantren’s financial administrators. The results showed an improvement in the administrators’ understanding of the importance of an orderly recording system, as well as an increase in the quality and consistency of financial reports. This mentoring activity had a positive impact on the financial accountability of the pesantren and served as a valuable learning experience for students in applying accounting theory in real-world contexts within religious and social institutions.